The Cys allele of the DRD2 Ser311Cys polymorphism has a dominant effect on risk for schizophrenia: Evidence from fixed- and random-effects meta-analyses - Glatt, Stephen J.; Jönsson, Erik G. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2006)
Previously we derived independent estimates of the effect of the dopamine D2 receptor (DRD2) Ser311Cys polymorphism on risk for schizophrenia using fixed‐ and random‐effects meta‐analyses. Both analyses identified a significant association between the Cys allele and schizophrenia, but neither included all available data. Furthermore, genotype data were not evaluated in either analysis, thus precluding any determination of the mode of inheritance. The present study was conducted to resolve discrepancies between the existing meta‐analyses, and provide more comprehensive and accurate estimates of the nature and magnitude of the influence of the Ser311Cys polymorphism on risk for schizophrenia. All discrepancies between the two sets of previously meta‐analyzed studies were identified and resolved to the mutual satisfaction of the authors, and the final dataset was analyzed independently by fixed‐ and random‐effects meta‐analyses. A total of 27 samples, comprising 3,707 schizophrenia patients and 5,363 control subjects, were included in the analyses of allelic association, while smaller numbers of studies and subjects were included in each of the genotypic association analyses. A significant effect of the Cys allele was observed under both fixed‐effects (odds ratio [OR] = 1.4; P = 0.002) and random‐effects (OR = 1.4; P = 0.007) models. Cys/Ser heterozygotes were at elevated risk for schizophrenia when compared to Ser/Ser homozygotes (fixed‐ and random‐effects OR = 1.4, ps ≤ 0.005), but Cys/Cys homozygotes were at no elevated risk relative to heterozygotes (OR = 1.0, ps ≥ 0.948). There was no evidence of heterogeneity, excessive influence of any single study, or publication bias in any of the analyses, suggesting that the effect of this DRD2 polymorphism on schizophrenia risk is reliable and uniform across populations, and our estimates of its magnitude are robust and accurate. © 2006 Wiley‐Liss, Inc.